Mewujudkan Pemberdayaan Masyarakat Melalui Pelatihan Perawatan Pesawat Udara Khususnya Mesin Turbin Gas Bagi Guru-Guru SMKN 12 Bandung - Lenny Iryani; Maria Fransisca Soetanto; Syarif Hidayat; Mochammad Luthfi; Budi Hartono; Radi Suradi Kartanegara; Teguh Wibowo; Yohanes Sinung Nugroho; Muhammad Rizki Zuhri; Citra Asti Rosalia; Zaim Sidqi Islami (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This program is aimed for teachers from SMK N 12 Bandung. Through this PKM (Community Service Program), it is expected that the training participants will gain insights and enhanced knowledge regarding aircraft maintenance, particularly the maintenance of gas turbine engines. The training was conducted at the Propulsion Laboratory, Aeronautical Engineering Hangar, Department of Mechanical Engineering, from October 12 to 16, 2021. The aircraft engine maintenance training began with a pre-test to assess participants' initial knowledge of aircraft engine maintenance. At the end of the training, a post-test was conducted to measure the improvement in their understanding and knowledge. The outcome of this PKM activity is a certificate of participation in the aircraft maintenance training, specifically focused on gas turbine engines.